2017
DOI: 10.1016/j.ajog.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of interpregnancy interval on infant mortality

Abstract: Background In Ohio the infant mortality rate is above the national average and the black infant mortality rate is more than twice the white infant mortality rate. Having a short interpregnancy interval has been shown to correlate with preterm birth and low birth weight, but the effect of short interpregnancy interval on infant mortality is less well established. Objective To quantify the population impact of interpregnancy interval on the risk of infant mortality. Study Design This was a statewide populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 23 publications
2
52
4
Order By: Relevance
“…Previous research using 1991 US birth certificate data showed an elevated association between short IPI (defined as <19 months) only and infant mortality . Similarly, more recent state‐based studies using 2003 revised birth certificate data also found similar associations between only short IPI (defined as either <18 months or <12 months) and infant mortality . In contrast to these studies, we observed a significant association between long IPI and increased risk of overall infant mortality.…”
Section: Commentcontrasting
confidence: 68%
“…Previous research using 1991 US birth certificate data showed an elevated association between short IPI (defined as <19 months) only and infant mortality . Similarly, more recent state‐based studies using 2003 revised birth certificate data also found similar associations between only short IPI (defined as either <18 months or <12 months) and infant mortality . In contrast to these studies, we observed a significant association between long IPI and increased risk of overall infant mortality.…”
Section: Commentcontrasting
confidence: 68%
“…[8][9][10][11]21,22,25,[27][28][29][34][35][36][37][38][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The majority of studies were conducted in the United States (n = 18), 11,21,25,[27][28][29][36][37][38]49,51,[54][55][56][57][58][59]62 78% of which used U.S. birth certificate data (n = 14). 11,21,…”
Section: Re Sultsmentioning
confidence: 99%
“…Nine of the 32 studies met criteria for good internal validity, [8][9][10][11]22,28,34,35,46 18 fair 21,25,27,29,36,37,[47][48][49][50][51][52][53][54]57,58,60,61 and five poor 38,55,56,59,62 (Table 1). Most studies included a limited set of covariates for adjustment, and no study accounted for all the study design considerations outlined above.…”
Section: Re Sultsmentioning
confidence: 99%
“…1 These unintended pregnancies are significantly more likely to have short interpregnancy intervals (<18 months apart) compared with pregnancies reported as intended (unadjusted odds ratios, 4.3 and 1.8, respectively). 1 Short interpregnancy intervals also increase risks for poor maternal and infant outcomes, 24 which makes the reduction in short-interval unintended pregnancies a public health priority.…”
mentioning
confidence: 99%